Proses Modernisasi Sosial dan Nilai Modernisasi Sosial pada Tokoh Ogbanje Ojebeta dalam Novel The Slave Girl Karya Buchi Emecheta - Eva Fatimah (Universitas Stikubank (UNISBANK) Semarang, 2015)
The objective of this research is to reveal the process and the value of modernization in character of Ogbanje Ojebeta. The analysis of this research uses sociological perspective and theory of modernization by Steven Vago. The result of the analysis reveal that Ogbanje Ojebeta experienced modernization by acculturation and the modernization value which she had is related to religion and occupation. Keywords: Character, Social Process, Social Value, Modernization